Adverse events due to unnecessary radiation exposure in medical imaging reported in Finland. Issue 4 (November 2020) - Tarkiainen, T.; Haapea, M.; Liukkonen, E.; Tervonen, O.; Turpeinen, M.; Niinimäki, J.
Abstract: Introduction: Adverse events in radiology are quite rare, but they do occur. Radiation safety regulations and the law obligate organizations to report certain adverse events, harm and near misses, especially events related to patients' health and safety. The aim of this study was to describe and analyse incidents related to radiation safety issues reported in Finland. Methods: The data were collected from incident reports documented by radiology personnel concerning notifications of abnormal events in medical imaging made to the Radiation and Nuclear Safety Authority between 2010 and 2017. During these eight years, 312 reports were submitted. Only events reported from radiology departments were included; nuclear medicine, radiotherapy and animal radiology cases were excluded. The final number of reports was 293 (94%). Results: The majority of the 293 approved reports were related to computed tomography (CT, 68.3%) and to X-ray examinations (27.6%). Altogether 82.9% of those irradiated were adults, most of whom were exposed to unnecessary radiation through CT (86.5%), 5.5% were children, and 4.4% pregnant women. The most common effective dose of unnecessary radiation was 1 mSv or less (89.7% of all examinations). The highest effective doses were reported in CT (from under 1 mSv–20 mSv and above). The reasons for the adverse events were incorrect identification (32%), incorrect procedure, site or side (30%); and human errors or errors of knowledge (20%). Conclusion: Adverse events occurred especially in CT examinations. It is important to collect and analyse incident data, assess the harmful events, learn from them and aim to reduce adverse events. Implications for practice: This study emphasizes the need for radiological personnel to obtain evidence-based information on adverse events and focus on training to improve patient safety.